Indigenous Dairy Product (Palopo): The Potential Utilization as A Carrier for Probiotics in The Development of Functional Foods is A Plausible Prospect - Sari, Sri Mutia; Wulandani, Baiq Rani Dewi; Kisworo, Djoko; Pertiwi, Eva Amalia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Palopo is a traditional food typical of West Sumbawa, West Nusa Tenggara Province, made from pure buffalo milk with a characteristic soft texture with the addition of eggplant (Solanum virgianium L) in the coagulation process. The use of probiotics and microorganisms in the milk fermentation process is part of the development of milk-based functional foods. This study aims to determine the microbiological properties of Palopo added with lactic acid bacteria as a functional food to determine the role and impact of microorganisms on the quality of Palopo. LAB viability data were analyzed by analysis of variance (ANOVA) using SAS software. If the treatment had a significant effect, then we continued with Duncan's difference test. The results of analysis of variance showed significant differences in LAB viability in Palopo. The highest number of LAB was found in Palopo, added with Streptococcus thermophilus (ST), with a total of 10,172 Log CFU/ml. Based on Duncan's further test, there was no significant difference in LAB viability in ST against LB and LP. Palopo without the addition of LAB was found to have viable LAB with a total of 2, 623 Log CFU/ml. So that LAB is concluded to be able to significantly improve the quality of Palopo products.